A rare case of patient with severe thrombocytopenia associated with sarcoidosis: a case study - Karpovich, Yulia; Ribadiya, Fenilkumar Nitinbhai; Tanna, Shalini Suresh; Trada, Darshi Yagnesh; Karpovich, Yury; Bogdanovich, Vladimir (International Journal of Research in Medical Sciences, 2023)
Thrombocytopenia is a problem causing drop in platelet counts through different mechanisms. Patients typically present with petechiae to systemic bleeding, which are indications of a low platelet count. A smaller percentage of drop may be asymptomatic. The major mechanisms include increased sequestration in the spleen, underproduction from the bone marrow, and peripheral destruction. Many etiological factors can cause this. Sarcoidosis is one of the most uncommon etiologies. A careful diagnosis is required because, if the condition is not treated, it can be fatal. Steroid therapy and platelet transfusions remain the mainstay of treatment. Here, we describe a patient who presented with signs and symptoms of severe thrombocytopenia, which further led to the diagnosis of sarcoidosis. An adult male presented to the emergency department with a rash that deteriorated throughout the day. Based on complaints and laboratory testing, severe thrombocytopenia was noted. After a detailed examination and history-taking, he was found to have sarcoidosis. In association with drug administration and sarcoidosis, this could have caused severe thrombocytopenia. Written consent was taken from the patient mentioned in the study. The study was approved by the hospital and institutional ethics committee. Thrombocytopenia is a disorder where platelet counts drop below 150×109/l due to many different mechanisms. Among different etiological factors, sarcoidosis is the rarest and may present with very severe thrombocytopenia and lead to fatal complications. Such patients require close monitoring and treatment. Corticosteroids and platelet transfusions can be used as treatments. In the presented case, the patient was successfully treated, and on subsequent follow-up, the patient’s condition improved. Manifestations of severe thrombocytopenia can be present even before the diagnosis of sarcoidosis. Further, the history of amoxicillin administration due to infection could have triggered the appearance of thrombocytopenia. Confirmation of sarcoidosis was made via biopsy. Multiple etiological factors that resulted in diagnostic ambiguity in our patient’s presentation include the diagnosis of sarcoidosis, a history of infection, amoxicillin, and mild splenomegaly. The patient’s treatment and recovery may indicate that corticosteroids, in conjunction with platelet transfusions, are beneficial. This is a novel case report of the presentation of severe thrombocytopenia, which was present even before the diagnosis of sarcoidosis.